Adaptações funcionais e bioquímicas de jogadores de futsal de alto nível em diferentes períodos da temporada - Tocchetto, Guilherme Lopes (2015)
The high-level sport requires a routine of intense training, high-levels players are exposed to various situations that may cause decline in their performance over a season. Therefore, the aim of this study was to verify functional and biochemical markers on elite level futsal players throughout a competition season. Eight players were analyzed statistically after being submitted to three maximal tests during the year: preseason (T1), competitive period (T2), and at the end of the season (T3). Functional parameters were assessed and blood sampling for cell count, lipid profile, inflammation, injury-related, and oxidative stress markers were performed before and after an maximum VO₂ test each time point. No differences were found for functional and lipid profile measurements. However, differences for total number of neutrophlis, monocytes, hemoglobin, creatine kinase, C-reactive protein, ischemia modified albumin, and advanced oxidation protein products between time points throughout the season were found. Blood lactate and lactate dehydrogenase levels showed differences within pre x post tests. Lower levels of inflammation, oxidative stress, and injury-related markers were found on T2 compared to T1 and T3, indicating that players were adapted to the training load. Although complementary studies are needed, it seems that routine-based biochemical markers may be used as training control means in this population.